Pengaruh Ekspektasi Pendapatan, Teknologi E-Commerce, dan Penggunaan Sistem Informasi Akuntansi Terhadap Keputusan Berwirausaha di Masa Pandemi Covid-19 - Ni Putu Evi Astari; I Gusti Ayu Intan Saputra Rini; I Gusti Ayu Ratih Permata Dewi (Universitas Warmadewa, 2025)
This research aims to identify the influence of income expectations, e-commerce technology, and the use of AIS on entrepreneurial decisions during the COVID-19 pandemic. The population in the research is students of the Faculty of Economics and Business at UNMAS Denpasar, UNHI, National Learning University, Warmadewa University, Mahendradata University, and Ngurah Rai University, class of 2019, with 98 respondents as the sample. The data analysis method used in this research is Multiple Linear Regression. Based on the research results, it can be seen that: income expectations have a positive effect, e-commerce technology has a positive impact, and the use of AIS has a positive effect on entrepreneurial decisions. Recommendations that can be given are that Private Universities in Denpasar City can improve student entrepreneurial decisions by increasing income expectations, e-commerce technology, and the use of accounting data systems.